Knowledge About Complications of Diabetes Mellitus and its Association with Treatment Compliance Among Type 2 Diabetics Visiting a Public Sector Diabetes Clinic - Mubashra Gull, Rafia Hussain, Mujtaba Haider Bukhari, Jamila Bibi, Aashi Mughal, Mubashra Gull, Rafia Hussain, Mujtaba Haider Bukhari, Jamila Bibi, Aashi Mughal (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Despite effective methods of treatment, half of the diabetic patients fail to achieve good glycemic control. Type 2 Diabetics who have knowledge about their disease and treatment can play an active role in their diabetes care and are more likely to achieve optimal blood glucose and HbA1c levels. The objective of this study is to assess knowledge of complications of type 2 Diabetes mellitus and its association with treatment compliance in patients visiting a public sector diabetes clinic. Material and Methods: The study was a descriptive correlational study conducted at the Diabetes Clinic of Benazir Bhutto Hospital that encompassed 180 participants who were positive for type 2 diabetes mellitus. The study took place in 6 months from February to July in 2018. The participants were selected by non-probability convenience sampling, and informed consent was taken from the participants. They were assessed by a questionnaire-based interview. Data were analyzed via the Statistical Package for Social Sciences (SPSS), version 22 by applying descriptive statistics. Results: Out of 180 participants, mean age was 51.53 years (72.8% females and 27.2% males), 46.7% were taking oral hypoglycemic agents while 53.3% were on insulin. Respondents compliant to anti-diabetic drugs were 73.8%. The main reasons for non-compliance include forgetting to take medicine (43.5%), side effects of medications (10.9%), feeling that too many medications were prescribed (10.9%), or high dose was given (8.7%), and interference with meal plans (8.7%). A higher score of knowledge was associated with better compliance with treatment. Conclusion: The knowledge of complications of diabetes and compliance to treatment is inadequate in patients visiting diabetes clinics. Those who have higher scores showed better compliance to the treatment. Keywords: Diabetes mellitus, knowledge, complications, treatment compliance